2003
DOI: 10.1258/095646203321605530
|View full text |Cite
|
Sign up to set email alerts
|

Routine questioning about non-consenting sex: a survey of practice in Australasian sexual health clinics

Abstract: The objectives of the study were, 1. To ascertain if sexual health physicians and practitioners believe a question concerning a past history of non-consensual sex should be asked routinely and are asking it. 2. To identify whether sexual health services have established protocols to integrate this question into practice. 3. To identify the barriers to this becoming part of a routine sexual health history. A questionnaire covering demographics, protocols and practice around asking the question and reasons for n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 4 publications
0
14
0
Order By: Relevance
“…We hypothesised that the ease and convenience of an online questionnaire -and the incentive of a chance to win a weekend in an upmarket hotel -would drive the response rate higher still, perhaps beyond the 70% achieved in surveys of physicians conducted by our colleagues 4,5 and others. 6 In the event, at the end of the first month, the overall response rate was 4.0%; even after the reminder letter and a second month, it only reached 8. Why did a well-planned and conducted survey produce such a low response rate?…”
mentioning
confidence: 94%
“…We hypothesised that the ease and convenience of an online questionnaire -and the incentive of a chance to win a weekend in an upmarket hotel -would drive the response rate higher still, perhaps beyond the 70% achieved in surveys of physicians conducted by our colleagues 4,5 and others. 6 In the event, at the end of the first month, the overall response rate was 4.0%; even after the reminder letter and a second month, it only reached 8. Why did a well-planned and conducted survey produce such a low response rate?…”
mentioning
confidence: 94%
“…Although there is very little literature on this matter as it relates to New Zealand men who have sex with men in general (Feehan et al 2001, Hurst et al 2003, there is no research into the issue as it relates to Maori men. As well as summarising the small number of published works existing in New Zealand literature, this paper offers new and insightful observations from interviews with eight Maori men who, at the time of interviewing, ranged in age from their early twenties to over fifty.…”
Section: Introductionmentioning
confidence: 99%
“…Although research indicates that sexual assault is prevalent across a wide range of populations and can have long-term harmful effects, it is not widely assessed in routine clinical practice (e.g., Hurst et al, 2003;Pruitt & Kappius, 1992). Although this review identified a number of screening and assessment instruments that are designed to assess for sexual trauma, these measures are rarely employed in clinical settings.…”
Section: Resultsmentioning
confidence: 99%
“…Estimated incidence and prevalence rates of sexual assault are likely underestimates of the actual number of occurrences, due in part to the low reporting rates of victims of sexual assaults (e.g., Casey & Nurius, 2006). Although clinicians generally agree that the assessment and awareness of a client's trauma history (e.g., child abuse, intimate partner violence, and sexual victimization) is important for diagnosis and treatment, questions concerning these experiences are often not asked (e.g., Hurst, MacDonald, Say, & Read, 2003;Pruitt & Kappius, 1992;Samuelson & Campbell, 2005). Knowledge of a client's trauma history can aid in accurate diagnosis and treatment in a number of ways, including determining the etiology of the presenting problem and the impact of the trauma experienced (e.g., Jacobson & Richardson, 1987).…”
mentioning
confidence: 99%